Analysis of Reservoir Regulation Capacity Based on Cascade POA Optimal Scheduling Model - HOU Jiaqi; CHEN Cong; TIAN Yuanyang; XIONG Yicheng (Renmin Zhujiang)
Due to the completion of the cascade reservoirs,the hydrological process of the basin has changed significantly,and the scheduling of the existing reservoirs has changed.The assessment of the regulation capacity of the existing reservoirs will help to re-define the role of the reservoirs in the runoff regulation.Taking Menkantan hydropower station and Datankou reservoir on Modaoxi Basin as examples,this paper proposes the concept of “virtual regulating storage”,and constructs a cascade POA optimal scheduling model to verify the regulation capacity of small hydropower stations.According to the calculated results,the amount of discarded water is reduced compared to that in the original operation mode,and the downstream reservoir's ability to regulate incoming water is effectively improved.The research results provide a reference for the verification of reservoir regulation capacity,and a mode to improve the power generation efficiency of small hydropower stations.